2023
DOI: 10.1002/slct.202301912
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Fe3O4 Magnetic Material Modified by Fulvic Acid and Its Adsorption Performance for Methylene Blue

Zeqing Wu,
Hongxian Fan,
Xiaoxue Hu
et al.

Abstract: In this paper, a kind of Fe3O4 magnetic nano material modified by fulvic acid (FA) was prepared and used for removing methylene blue in wastewater. The structure and morphology of the material were characterized by FT‐IR, PXRD, BET, XPS, VSM, SEM and TEM. The results showed that FA successfully coated on the surface of Fe3O4 magnetic nano particles. The newly prepared magnetic material had large specific surface area and porous structure. The specific surface area of the material was 92.15 m2/g. The average po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing the efficiency by increasing the number of steps can be related to the saturation of adsorbent sites or damage to sites active in the adsorbent. [64,65] In previous studies, [66][67][68][69][70][71][72][73][74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Adsorbents Recyclementioning
confidence: 99%